HoloEasy, a web application for computer generated holograms (2018)
If the appropriate phase and/or amplitude profile is placed on a Diffractive Optical Element (DOE) it can practically generate an image of an object (hologram) by diffraction of the light. The problem of generating computer holograms consists of calculating numerically the profile of phase and/or amplitude with which the DOE should be built. Computer Generated Holograms (CGH) can be used to construct general-purpose optical elements in the sense that they serve to transform a spatial distribution of light into any other. In this way, they are used in optical communication systems, laser machining, laser welding, optical readers, human vision, data storage and visualization, image processing, among others. Unlike the optical techniques for generating holograms, in the CGH both the desired image and the phase and/or amplitude distribution are calculated numerically. In this work, a web environment application has been developed to calculate the phase changes that a coherent beam of light must undergo when incident on a DOE, so that it is transformed by Fraunhofer diffraction, in the hologram of an object. We use an algorithm with iterative Fourier transformations (IFTA) that uses regulation and stabilization parameters can be chosen by the user. In addition, the user has the freedom to choose holograms for optical applications (free of speckles) generating initial diffusers of a limited band and without phase singularities. © Springer Nature Switzerland AG 2018.